Changes in Yugoslavia’s Form of Government - Kutlešić, Vladan M. (Sociološki pregled, 2019)
During its existence, Yugoslavia went through all forms, sub-forms and elements of state form found comparatively and theoretically. As such, its identity and subjectivity was changed ofen and to a signifcant extent. During the 85 years of its existence, Yugoslavia was a monarchy (of all three possible varieties – absolute, consitutional and parliamentary) and a republic, it was a unitary state of various varieties (from deconcentration to assymetrical decentralization) and a complex state (from centralized federation to real union). It was also an autocracy and democracy of various degrees. Yugoslavia was a state of various types of unifed and divided authority. The most numerous changes were of various types of federal state sub-forms and of the position of executive power in the period of unity of powers. Such a pronounced and signifcant dynamic was obviously caused by a complex and diverse governmental structure which was comprised of elements with diﬀering governmental and legal histories and heritages, causing contradictions and disharmonies that required a constant search for more suitable forms. Regarding the changes in the organization of power and state form between 1943 and 1963, there was an obvious ideological inﬂuence of the soviet model, and from 1968 until 1974, there was a clear presence of political voluntarism in relation to the form of federalism and territorial and political autonomy. Signifcant changes in the strenght of the executive power, especially of the president of the republic in the period between 1963 and 1992 exceeded the conceptual bounds of a democratic unity of power into the non-democratic unity of power, reaching autocractic levels afer 1974, when the position of the president was granted for life via the constitution.
Keywords: state; power; governance; organization; order; Yugoslavia